(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
The article discusses the concepts of "euphemism" and "taboo" in linguistics; the meaning of these two concepts that represent the public life of the people in connection with traditions and mentality. These two concepts that they are ethnolinguistic terms originating from cultural and linguistic sources is also discussed. Furthermore, It is concerned about the role of these concepts in the lexicon of the Uzbek and English languages